THE EFFECT OF SEVERAL NON-OXIDIZING BIOCIDES ON FINE PAPER WET-END CHEMISTRY - Patrick Huber; Bruno Carré; Elisa Zeno (BioResources, 2010)
Biocide programs have become necessary in most fine paper manufacturing circuits, as drastic reduction of fresh water consumption in the industry enhances microbial development. Depending on their chemical nature, biocides may interfere with typical wet-end chemistry additives and furnish. A reference wet-end chemistry was set (including fixing aid, dry strength aid, sizing agent, and retention system), then biocides were added to the furnish (bleached virgin fibres + mineral filler) prior to handsheet making. Four of the tested biocides (organo-sulfur, dibromonitrilopropionamide, isothiazoline, and glutaraldehyde) were not found to interact with wet-end chemistry. On the other hand, the tested quaternary ammonium salt biocide showed very detrimental effects: it reduced filler retention in the sheet, decreased sheet strength, and destroyed sizing (sheet hydrophobicity).